Female leadership in sports clubs - Alfonso Martínez-Moreno; Francisco Cavas-García; Francisco Cano-Noguera; Arturo Díaz-Suárez (European Journal of Government and Economics (EJGE), 2020)
The objective of this study was to determine the type of leadership applied by the directors of amateur sports clubs. This quantitative, descriptive and cross-sectional study was carried out on a sample of 48 directors of sports clubs in total: 23 (47.91%) belonging to collective sports clubs and 25 (52.08%) to individual sports clubs. The study administered the MLQ-X5 Multifactor Leadership Questionnaire (45 items). The answers are collected on a Likert scale ranging from 0 (never) to 4 (almost always). The results indicated that the directors opt for a transformational leadership style (3.24), preferably followed by the corrective leadership type (3.18) and almost the same level as the developer type (3.17). The study concluded that the collective sports directors opt for the style of transformational leadership by being proactive and promoting the achievement of extraordinary goals.
Keywords: L83; D71; D91; 330; equality; management; satisfaction; sport; women